Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1007/978-1-4939-9136-5_15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assays to Measure the Membrane Tethering and Lipid Transport Activities of the Extended Synaptotagmins

Abstract: The three extended synaptotagmins (E-Syts) are endoplasmic reticulum (ER)-localized membrane proteins that mediate tethering of the ER to the plasma membrane (PM) via C2 domain-dependent interactions regulated by Ca2+ and/or PI(4,5)P2. The E-Syts also contains a Synaptotagmin-like Mitochondrial lipid-binding Protein (SMP) domain, a lipid-harboring module through which they mediate lipid transport between the two adjacent membranes. Here, we describe in vitro liposome-based methods to study the membrane tetheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(36 reference statements)
2
5
0
Order By: Relevance
“…The loss of PM specific phospholipid species is consistent with a role of ER-PM contacts in coordinating both phospholipid synthesis and transfer. All E-Syt family members feature a SMP domain that dimerizes and transports glycerolipids in vitro (Lee & Hong, 2006;Toulmay & Prinz, 2012;Schauder et al, 2014;Saheki et al, 2016;Yu et al, 2016;Bian et al, 2018;Bian & De Camilli, 2019;Qian et al, 2021). In particular, a recent study demonstrated the ability of the Tcb3 SMP domain to transport phospholipids in vitro (Qian et al, 2021), consistent with our in vivo experiments.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The loss of PM specific phospholipid species is consistent with a role of ER-PM contacts in coordinating both phospholipid synthesis and transfer. All E-Syt family members feature a SMP domain that dimerizes and transports glycerolipids in vitro (Lee & Hong, 2006;Toulmay & Prinz, 2012;Schauder et al, 2014;Saheki et al, 2016;Yu et al, 2016;Bian et al, 2018;Bian & De Camilli, 2019;Qian et al, 2021). In particular, a recent study demonstrated the ability of the Tcb3 SMP domain to transport phospholipids in vitro (Qian et al, 2021), consistent with our in vivo experiments.…”
Section: Discussionsupporting
confidence: 88%
“…The E-Syt proteins, as well as their budding yeast orthologs, named tricalbins, are anchored in the ER membrane via a N-terminal hairpin anchor (Giordano et al, 2013) and interact with the PM in a phosphoinositide lipid-and Ca 2+ -dependent manner via their multiple C-terminal cytoplasmic C2 domains (Chang et al, 2013;Giordano et al, 2013;Idevall-Hagren et al, 2015;Saheki et al, 2016;Bian et al, 2018). They also feature a central cytosolic synaptotagmin-like, mitochondrial (SMP) domain that dimerizes and contains a deep hydrophobic groove previously shown to bind and transport lipids in vitro (Schauder et al, 2014;Saheki et al, 2016;Yu et al, 2016;Bian et al, 2018;Bian & De Camilli, 2019). While cellular roles of E-Syt proteins as ER-PM tethers are described (Giordano et al, 2013;Fern ández-Busnadiego et al, 2015), roles of the E-Syts in membrane lipid dynamics in vivo are enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…The specific loss of PM phospholipid species is consistent with a role of the Tcb proteins in coordinating phospholipid synthesis and transfer at ER-PM contacts. All E-Syt family members feature a SMP domain that dimerises and transports glycerolipids in vitro (Lee and Hong, 2006; Toulmay and Prinz, 2012; Schauder et al, 2014; Saheki et al, 2016; Yu et al, 2016; Bian et al, 2018; Bian and De Camilli, 2019; Qian et al, 2021). In particular, a recent study demonstrated the ability of the Tcb3 SMP domain to transport phospholipids in vitro (Qian et al, 2021), consistent with our in vivo experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The E-Syt proteins, as well as their budding yeast orthologs, named tricalbins, are anchored in the ER membrane via a N-terminal hairpin (Giordano et al, 2013) and interact with the PM in a phosphoinositide lipid- and Ca 2+ -dependent manner via their multiple C-terminal cytoplasmic C2 domains (Chang et al, 2013; Giordano et al, 2013; Idevall-Hagren et al, 2015; Saheki et al, 2016; Bian et al, 2018). They also feature a central cytosolic synaptotagmin-like, mitochondrial (SMP) domain that dimerizes and contains a deep hydrophobic groove previously shown to bind and transport lipids in vitro (Schauder et al, 2014; Saheki et al, 2016; Yu et al, 2016; Bian et al, 2018; Bian and De Camilli, 2019; Qian et al, 2021). Whilst cellular roles of E-Syt proteins as ER-PM tethers are well-described (Giordano et al, 2013, Fernández-Busnadiego et al 2015), precise roles of the E-Syts the control of membrane lipid dynamics in vivo are enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…A shuttle mechanism, as described above, likely operates in E-Syt as the 90Å-long SMP dimer is too short to span the distance between membranes ( Schauder et al, 2014 ). E-Syts were found to mediate the transport of glycerophospholipids in a bidirectional manner using in vitro assays ( Saheki et al, 2016 ; Yu et al, 2016 ; Bian et al, 2018 ; Bian and De Camilli, 2019 ). E-Syts might also participate in mechanisms altering lipid composition.…”
Section: Er-pm Contact Sites In Neuronsmentioning
confidence: 99%